2008
DOI: 10.1109/ted.2008.2006533
|View full text |Cite
|
Sign up to set email alerts
|

Design and Realization of a Fully On-Chip High-$Q$ Resonator at 15 GHz on Silicon

Abstract: Abstract-We develop and demonstrate an on-chip resonator working at 15 GHz with a high quality factor (Q-factor) of 93.81 while only requiring a small chip size of 195 μm × 195 μm on Si by using our new design methodology. In our design, unlike previous approaches, we avoid the need for any external capacitance for tuning; instead, we utilize the film capacitance as the capacitor of the LC tank circuit and realize a fully on-chip resonator that shows a strong transmission dip of > 30 dB on resonance as require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…We presented a complete description of our circuit model given in figure 1(c), and the characterization of the RF device in our previous studies [6,11]. In this work, to achieve a high Q-factor, we used the same methodology from microwave perspective as in our previous studies [6,11]; further details of the RF design can also be found in the literature [12][13][14][15][16][17][18][19]. In this circuit model, C film is the capacitance between the coil and the substrate as in (1), as depicted in figure 1(b), and C S and L S denote the capacitance between adjacent coils and the inductance of the spiral coil, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…We presented a complete description of our circuit model given in figure 1(c), and the characterization of the RF device in our previous studies [6,11]. In this work, to achieve a high Q-factor, we used the same methodology from microwave perspective as in our previous studies [6,11]; further details of the RF design can also be found in the literature [12][13][14][15][16][17][18][19]. In this circuit model, C film is the capacitance between the coil and the substrate as in (1), as depicted in figure 1(b), and C S and L S denote the capacitance between adjacent coils and the inductance of the spiral coil, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…R S and R Si are the resistances of the coil and the substrate, respectively. We use R P and C P for the circuit conversions [6,11] and calculate them as in (2) and (3). Finally combining all these, we find the Q-factor of the inductor (Q ind ) as in (4).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Among their advantages is the ability to obtain higher quality factors ͑Q factors͒, and sharper and deeper dips on resonance in their transmission using SRR compared to traditional rf structures that we previously used ͑e.g., rectangular and circular coils͒. [17][18][19] This makes metamaterials very well suited for telemetric sensing applications. Furthermore, metamaterial architecture enables us to achieve higher resonance frequency shifts, leading to higher sensitivity and better linearity, compared to our previous rf sensor structures.…”
mentioning
confidence: 99%
“…17,18 Using microwave probes, we demonstrated the proof-of-concept principle of utilizing the resonance frequency shift 19 via on-chip resonators serving as sensors. In this paper, we present the proofof-concept of fully telemetric resonance frequency shifts using our metamaterial sensors.…”
mentioning
confidence: 99%